Ultrafast Charge Dynamics in Mixed Cation – Mixed Halide Perovskite Thin Films. Issue 22 (27th September 2018) - Minda, Iulia; Horn, Jonas; Ahmed, Essraa; Schlettwein, Derck; Schwoerer, Heinrich
Abstract: Perovskite based photovoltaic devices are popularised by the rapid increase in their efficiencies. Understanding the fundamental physics and chemistry processes occurring upon excitation is key. We monitored the temporal evolution of the population and depopulation dynamics of various electronic states in FA0.85 MA0.15 PbI2.55 Br0.45 by means of ultrafast transient absorption spectroscopy in the visible and near infrared spectral regions in order to build a fully consistent charge dynamics model of the initial photoprocesses. Upon photoexcitation with 3.2 eV photon energy, hot electrons and holes are generated in the lowest conduction and highest valence bands, away from the bandgap, and cool to the band edges with a time constant of 500 fs. Geminate recombination of excitons occurs with a time constant of 66 ps, which increases to approximately 130 ps at the optical bandgap. From a systematic study of the excited state population dynamics and its dependence on charge carrier density, we determined the nonlinear recombination rate constants characteristic to FA0.85 MA0.15 PbI2.55 Br0.45 . The coefficient describing the non‐geminate recombination of free electrons and holes is independent of the k vector as well as the charge carrier density and equal to 1×10 −10  s −1  cm 3, while the Auger recombination coefficient decreases with increasing charge carrier density in the range of (2–50)×10 −32  s −1  cm 6 . Abstract : The ultrafast charge dynamics following photoexcitation of the mixed‐ion perovskite FA0.85 MA0.15 PbI2.55 Br0.45, an effective photoabsorber in high‐efficiency perovskite solar cells, are studied using femtosecond transient absorption spectroscopy in the visible and near‐IR spectral regions.